Pre-service teachers’ views of an ideal teacher for a fast-changing world - Pumzile Lydia Mello; Sarah Gravett (Perspectives in Education)
This article reports on a study that explored final year preservice teachers’ conceptualisations of an ideal teacher for a fast-changing world. The study was framed by literature on reflective practice. A basic qualitative research design was used to examine how the preservice teachers constructed meaning of the phenomenon under study. Data were collected via semi-structured interviews and thorough analysis of the preservice teachers’ research projects on the topic. The findings are that ideal teachers for a fast-changing world must: be adaptable; be digitally literate and fluent; encourage agency in the teaching and learning environment; use innovative teaching methods; and value continuous professional development. The findings lead to the question as to whether teacher education programmes pay sufficient attention to preparing pre-service teachers for the fast-changing world, in the curriculum and through practices taught.